Educational Impact of Targeted Neonatal Echocardiography and Hemodynamics Programs on Neonatal-Perinatal Medicine Fellows - Friedmann, Isabel; McNamara, Patrick J.; Bhattacharya, Soume; Cheng, Anita (American Journal of Perinatology, 2022)
Objective Targeted neonatal echocardiography (TNE) is a real-time cardiac imaging modality used by a hemodynamics program to aid in diagnosis, treatment, and monitoring of neonatal cardiovascular illness. This study aimed to describe trainees' perspectives on existing hemodynamics education and perceived impacts of TNE and hemodynamics services on their education.Study Design This was a mixed quantitative and qualitative study that surveyed neonatal-perinatal medicine (NPM) fellow trainees in Canada and the United States, at programs both with and without a hemodynamics service.Results Ninety-two fellows responded to the survey, of whom 24 (26%) were enrolled in a program with an active hemodynamics service, 64 (70%) were training at a program without a hemodynamics service, and 4 (4%) were unsure. Trainees at centers with a hemodynamics service were more satisfied with their cardiovascular physiology education (91 vs. 69%, p = 0.040). Twenty-five percent of all trainees felt they do not have sufficient hemodynamics training to prepare them for independent practice. Areas of knowledge gaps were identified. Bedside teaching combined with didactic teaching was identified as useful means of teaching.Conclusion Most trainees believed that TNE and a hemodynamics service are valuable educational assets. Thoughtful curriculum design for real-time and consolidation learning, with specific emphasis on content gaps, should be considered.Key Points
Keywords: cardiovascular education; targeted neonatal echocardiography; neonatal-perinatal medicine; hemodynamics